Microfinance training and the number of loans received by SMEs. An empirical evidence from emerging economy - Sani, Habibu; Mohd Khan, Shazida Jan; Zamzuri Noor, Mohd Saifoul (Prague Development Center, 2018)
The objective of this study is to examine the impact of Microfinance training, Trust and Social ties on the Number of loans received by small and medium-scale enterprises (SMEs) in developing economies. The Poisson regression model is used as the method of analysis. 195 SMEs in North-Eastern Nigeria form the sample of the study based on two-stage sampling and simple random sampling technique. The results reveal that Social ties, Location, and Nature of operation have a significant positive relationship with the Number of loans receives by SMEs. Similarly, the Number of training and Trust have significant positive impact on the Number of loans received; however, they demonstrate the least impact as compared with the other variables based on the level of significance.